Womanhood Policing In Sport And Human Rights Violations : A Look At Differences In Sexual Development (DsD) Regulations By World Athletics And The Transgender Ban Through A Human Rights Lens - Songuro, Ayodele (University of Pretoria, 2022)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2022.